Corpus-based cultivation of critical language awareness: A case study on English film subtitles - Su, Tingting; Abdou Moindjie, Mohamed; Kaur Mehar Singh, Manjet (Journal of Interdisciplinary Studies in Education, 2024)
This study examines the use of English film subtitles to cultivate critical language awareness (CLA) and enhance language skills via a corpus-based approach. Creating and analyzing a specialized corpus of film subtitles reveals the cultural, social, and ideological dimensions of language usage. The findings show that film subtitles provide an authentic context for language learning, improving the comprehension of diverse linguistic expressions. This approach fosters cultural awareness and critical thinking, bridging linguistic proficiency and cultural understanding. While focusing on English, the methodology is adaptable to various languages. This research offers novel insights into language education, particularly in applying corpus-based methods for CLA and practical language skill enhancement.